Persepsi peternak sapi dalam pemanfaatan kotoran sapi menjadi bi-ogas di Desa Sekarmojo Purwosari Pasuruan - Amang Fathurrohman; Muh. Aniar Hari S; Moh. Awaludin Adam (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The aim of this research was to know the perception of cattle farmers towards dung utilization as biogas in Sekarmojo village, Purwosari, Pasuruan. The study used qualitative method with phenomenological approach. The data were collected from cattle farmers in Mojo hamlet, Sekar Mojo village, Pasuruan regency through interview, documentation and observation. The result showed that farmers in Sukorejo village did not utilize cow dung as biogas due to lack of knowledge about biogas. Instead of it, they prefered use it directly as fertilizer in their fields. Moreover, there were many negative perceptions such as village myth, expensive cost for biogas installation, worried of failure to sustain the biogas and traumatic of gas explosion.Keywords : biogas, dung, village, farmer, cattle